Valorization of keratin biofibers for removing heavy metals from aqueous solutions. Issue 7 (April 2019) - Zhang, Helan; Carrillo, Fernando; López-Mesas, Montserrat; Palet, Cristina
Four common waste keratin biofibers (human hair, dog hair, chicken feathers, and degreased wool) have been used as biosorbents for the removal of heavy metal ions from aqueous solutions. Different parameters of the biosorption processes were optimized in batch systems. For multiple-metal systems, consisting of a mixture of eight metal ions [Cr(III), Mn(II), Co(II), Ni(II), Cu(II), Zn(II), Cd(II), and Pb(II)], the total metal biosorption increased in the order: degreased wool > chicken feathers > human hair > dog hair. From the kinetic models tested, the pseudo-second-order model provided better results. Furthermore, biosorption isotherms of Pb(II) with the different keratin biofibers fitted the Langmuir model. Surface morphology of the biosorbents were analyzed before and after the sorption using Fourier transform infrared spectroscopy and scanning electron microscopy. The keratin biofibers tested are potentially good sorbents of metal ions, with degreased wool and chicken feathers being the more efficient ones.